Potential of valsartan+sacubitril therapy in hypertensive heart disease - A. G. Ovchinnikov; A. D. Gvozdeva; A. V. Potekhina; M. V. Vitsenya; F. T. Ageev (Российский кардиологический журнал)
The course of hypertension is often complicated by left ventricular hypertrophy (or hypertensive heart disease, HHD). The main “corridor” of natural HHD is development of heart failure with preserved ejection fraction (HFpEF). With HFpEF, the bioavailability of natriuretic peptides (NP) is significantly reduced, as a result of which the activity of cGMP-PKG signaling pathway, which plays a key role in maintaining normal diastolic function, weakens. It is possible to increase the activity of this pathway using the neprilysin inhibitor sacubitril. In case of HFpEF, the greatest efficacy from valsartan+sacubitril therapy should be expected in patients with severe concentric LVH, who have the most pronounced natriuretic peptide deficiency. Valsartan+sacubitril therapy has a clear hypotensive effect, causes a reversal of left ventricular hypertrophy and fibrosis. Since no effective treatment has yet been found for HFpEF, the main way for HHD treatment should be to prevent the diastolic dysfunction progression, which justifies valsartan+sacubitril therapy starting from the early/ asymptomatic stages.